ANALISIS WACANA KRITIS SARA MILLS TERHADAP REPRESENTASI NIKITA MIRZANI DALAM PEMBERITAAN MEDIA ONLINE INDONESIA - Sumiati Agphyra S; Asep Nurjamin; Ari Kartini (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study is grounded in the tendency of online media to represent female public figures in ways that often contain gender bias and specific moral constructions. News coverage of Nikita Mirzani serves as a relevant case for examining how women are positioned within legal and social discourse through media framing. The purpose of this research is to analyze the representation of women by exploring the construction of subject, object, writer, and reader positions in news texts using Sara Mills' critical discourse analysis approach. This research employs a qualitative descriptive method, with data collected through documentary study of news articles published by Detik.com, Mind of the People, Kompas.com, and CNN Indonesia. The analysis was conducted by identifying patterns in the placement of female actors within the texts and comparing the narrative strategies used by each media outlet. Data validity was ensured through source triangulation and repeated readings to maintain consistency in interpretation. The findings reveal significant differences in representational construction. Detik.com and CNN Indonesia tend to portray Nikita Mirzani as an active, assertive, and rational subject in responding to legal issues, while Pikiran Rakyat and Kompas.com emphasize her emotional dimension and moral positioning as a public woman. These findings indicate that women's representation in the media remains influenced by patriarchal values that shape power relations within news narratives. This study highlights the importance of critical media awareness in fostering fairer and more gender-sensitive representations, while also contributing to the development of critical discourse analysis in the context of Indonesian digital media.